Tata Kerja Pembentukan Fatwa-Fatwa MUI: Melacak Karakteristik Ushul Fiqh MUI dalam Memutuskan Hukum - Taufiqur Rahman; Miftakur Rohman (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2021)
The Indonesian Ulama Council is a forum or assembly that brings together scholars, zu'ama> and Indonesian Muslim scholars to unite the movements and steps of Indonesian Muslims in realizing common goals. The Indonesian Ulema Council was established on July 26, 1975 in Jakarta. The presence of MUI as a place of reference for Muslims in Indonesia in dealing with and resolving and deciding a law that occurs in Indonesian society is a necessity. Therefore, there have been many legal fatwas born from this organization since the beginning until this modern era. Be it in matters of religious practice, social, economics, science, medicine and even the political realm. The development of Islamic legal thought in Indonesia faces complex dynamics due to the unique socio-political system that exists. Thus, the MUI fatwa itself is not uncommon or often counter-productive both externally and internally by Muslims themselves. The author in this study intends to critically describe the MUI fatwa itself, both in terms of its existence and its manhaj.